Komparasi Pemahaman Konsep Persamaan Kuadrat antara Problem-Based Learning dan Pembelajaran Langsung - Jeilan Cicilia Tumei; Ichdar Domu; Rosauli Novalina Samosir (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aims to determine the difference in students' conceptual understanding of quadratic equations between those taught with the Problem-Based Learning (PBL) model and those taught with direct instruction. It was motivated by students' low conceptual understanding in mathematics, largely caused by the dominance of teacher-centered learning. A quantitative approach was employed using a quasi-experimental method with a pretest-posttest control group design. The sample comprised two grade IX classes selected through cluster sampling, namely one experimental and one control class, each consisting of 30 students. Data were collected through an essay-type conceptual understanding test validated by experts. Normality (Shapiro-Wilk) and homogeneity (Levene) tests were run using SPSS, while the hypothesis was tested with an Independent Samples T-Test at a 0.05 significance level. The results showed a t-value of 4.838, greater than the t-table value of 1.671, so H0 was rejected and H1 accepted. The experimental class mean post-test score (74.17) exceeded that of the control class (69.93). Thus, students taught with PBL achieved better conceptual understanding of quadratic equations, suggesting PBL is an effective alternative for mathematics learning.